A NORM STUDY ON PHYSICAL AND MOTOR DEVELOPMENTS IN BASKETBALL SCHOOL CHILDREN - Kirandi, Ozlem; Şahin, Mustafa (Acta Scientiae et Intellectus, 2024)
The aim of this study is to define a norm on physical development and motor performances of children who attend basketball school, aged 7 to 14. This norm study matters because it will be a reference to other researchers who will be researching the relevant area. 638 children (387 boys and 251 girls) participated in the study in the province of Istanbul, who participated in the summer sports schools of the Istanbul Metropolitan Municipality and written consent form was taken from parents of the children. The study is a cross-sectional study in which the status determination was done by using quantitative data. Body lengths, body weights, height while seating, flexibilities, hand and foot lengths, claw strength, shoulder widths, and fathom lengths were measured for physical development after the birth dates of the children and their dominant hand and feet were recorded. The data of the study was formed by measuring the balance skills, vertical jump skills, quickness and speed parameters in order to determine the motor performances. The norm study was completed by conducting frequency analysis on the obtained data. As a result of the study, it was determined that children aged between 7 - 14 years who attended basketball school used predominantly right hand and right leg, physical development and motor performances were similar to international standards.